Warunki przyswajania innowacji w przedsiębiorstwie - Penc, Józef (Wydział Prawa i Administracji UAM, 1983)
Problems of acceleration and propagation of innovational processess facilitating saving worktime, material and energy, increase of production, improvement of its quality as well as reduction of prime and social costs are of a particular importance in the period of intensive transformations of our economy. The author discusses various interpretations of transformations which are known as innovations, motives and barriers of their introduction under differing conditions and particularly, in light of the economic reform. He indicates at failures of the previously used and of the presently introduced systems of motivating innovational processes in enterprises, lack of a proper social atmosphere for their intensification and propagation, and at a phenomenon of resistance to change related to inefficient organization and a low susceptibility to innovations caused by a low effectiveness of stimuli and their low effect on inovational activity of employers. The author also presents his own propositions on modifying rules of paying bonuses for technical, organizational progress accounting in particular for a role played by psycho-social motivations. In conclusion the author postulates a need of system controls of activity, novelty and inventiveness of employees, a success in this sphere can only be brought by programmed activities, integrally linked with aspirations to fulfil own needs of workers and with a development and effectiveness of enterprise, the activity being the very source of thrift and -satisfaction.
Conditions of adopting innovations in enterprise